Role of IGF2BPs in head and neck squamous cell carcinoma - Wu, Kainan; Chang, Fen; Li, Wenming; Su, Tongdong; Lei, Dapeng (Frontiers in Oncology, 2022)
IGF2BPs belongs to a family of conserved RNA-bound oncoembryonic proteins that play a crucial part in various aspects of cell function, such as cell migration, morphology, metabolism, proliferation and differentiation. Recent studies have shown that IGF2BPs play a role as a member of m6A reader. m6A is the most abundant modification in RNA epigenetics, which is closely related to a family of RNA-binding proteins. These proteins are fell into three categories—writers, readers and erasers. In the present study, IGF2BPs play an important role in tumor metabolism, especially in head and neck squamous cell carcinoma (HNSCC) metabolism. In this paper, the basic structure of IGF2BPs, its role in the development of HNSCC, molecular mechanism, research progress and research prospect of IGF2BPs in HNSCC are reviewed, which will providing new ideas for further study of IGF2BPs.